Functional Superior Mesenteric Artery Syndrome Induced by an Optional IVC Filter - Adam Shen; Dina Tabello; Nishant Merchant; Joseph V. Portereiko; Alfred Croteau; Jonathan D. Gates (Case Reports in Surgery)
This patient suffered multiple injuries in a motor vehicle crash. She had an optional IVC filter placed in the usual fashion and location which resulted in a functional obstruction of the third part of the duodenum much as one would expect with a Superior Mesenteric Artery (SMA) syndrome. The symptoms persisted over the sixteen-day filter dwell time and resolved completely with the retrieval of the filter.